A random encoding method for secure data communication: An extension of sequential coding. (4th July 2021) - Chaturvedi, Atul; Shukla, Varun; Misra, Manoj Kumar
Abstract: The security of data communication is very important in all aspects. V. Shukla et al. had proposed a secure sequential coding method. They have shown the results for text secret messages only. In this paper, firstly we extend their scheme by showing the results for image secret messages. Secondly, we upgrade their scheme by proposing the similar method by using random encoding. Random encoding enhances the level of security. A separate section is provided for security analysis and associated advantages.